A decentralized model of Wind turbine optimization. Issue 2 (April 2020) - Dhunny, AZ; Allam, Z; Lollchund, MR; Dookhitram, K; Rughooputh, SDDV
The decoupling of energy prices from fossil fuel is slowly making its way as investment is poured into renewable energy sources. Small Island Developing States are gaining in both stability and cost from this momentum but face threat from the same unsustainable centralization practices. A decentralized framework is proposed for Small Island Developing States aimed at achieving grid stability and in attracting independent financing mechanisms. This framework is applied from a Wind perspective and to ensure replicability on all types of terrains, and the model is analysed through three case studies: high-rise buildings, flat terrains and Gaussian terrains. This study provides a novel framework and a general solution for Wind farming over different terrain layouts including forbidden regions and complex topography.